Lithotripsy of Calcified Aortic Valve Leaflets by a Novel Ultrasound Transcatheter-Based Device - Bernava, Giacomo; Fermi, Enrico; Gelpi, Guido; Rizzi, Stefano; Benettin, Davide; Barbuto, Marianna; Romagnoni, Claudia; Ventrella, Domenico; Palmieri, Maria Chiara; Agrifoglio, Marco; Polvani, Gianluca; Bacci, Maria Laura; et al. (Frontiers in Cardiovascular Medicine, 2022)
The increasing incidence of calcific aortic valve disease necessitates the elaboration of new strategies to retard the progression of the pathology with an innovative solution. While the increasing diffusion of the transcatheter aortic valve replacements (TAVRs) allows a mini-invasive approach to aortic valve substitution as an alternative to conventional surgical replacement (SAVR) in an always larger patient population, TAVR implantation still has contraindications for young patients. In addition, it is liable to undergo calcification with the consequent necessity of re-intervention with conventional valve surgery or repeated implantation in the so-called TAVR-in-TAVR procedure. Inspired by applications for non-cardiac pathologies or for vascular decalcification before stenting (i.e., coronary lithotripsy), in the present study, we show the feasibility of human valve treatment with a mini-invasive device tailored to deliver shockwaves to the calcific leaflets. We provide evidence of efficient calcium deposit ruptures in human calcified leaflets treated ex vivo and the safety of the treatment in pigs. The use of this device could be helpful to perform shockwaves valvuloplasty as an option to retard TAVR/SAVR, or as a pretreatment to facilitate prosthesis implantation and minimize the occurrence of paravalvular leak.